2002
DOI: 10.5483/bmbrep.2002.35.5.494
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Administration of Conjugated Linoleic Acid Reduces Liver Triglyceride Concentration and Phosphatidate Phosphohydrolase Activity in OLETF Rats

Abstract: The present study explored the short-term effects of dietary conjugated-linoleic acid (CLA) on liver lipid metabolism in starved/refed Otsuka Long Evans Tokushima Fatty (OLETF) rats. Male OLETF rats (12 weeks old) were starved for 24 hours, then refed for 48 hours with either a CLA diet [7.5% CLA and 7.5% Safflower oil (SAF)] or a SAF control diet (15% SAF). The results demonstrated a 30% reduction of hepatic triglyceride (TG) concentration in the CLA group when compared to the control group. Liver cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…1) in fa/fa Zucker rats, consistent with other studies using rat models of obesity and insulin resistance (9)(10)(11)(12). Although the progression of NAFLD was not monitored by histology in this study, fasting serum ALT and alkaline phosphatase were lower (54 and 64%, respectively) in fa/fa CLA-fed rats compared with fa/fa CTL-fed rats (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1) in fa/fa Zucker rats, consistent with other studies using rat models of obesity and insulin resistance (9)(10)(11)(12). Although the progression of NAFLD was not monitored by histology in this study, fasting serum ALT and alkaline phosphatase were lower (54 and 64%, respectively) in fa/fa CLA-fed rats compared with fa/fa CTL-fed rats (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…CLA induces hepatic steatosis in normal-weight mice (7,8) but ameliorates hepatic steatosis in insulin-resistant obese rats (9)(10)(11)(12). These differing outcomes may be due to various factors including species-specific and age-related responses, varying levels and duration of CLA supplementation, and the background diet.…”
mentioning
confidence: 91%
“…Feeding CLA also reduced liver triacylglycerol levels in rats (Rahman et al, 2002) and, in rodents, studies have suggested that CLA increased fatty acid oxidation via an increase in CPT-I activity (Rahman et al, 2001;Degrace et al, 2004). However, neither CPT-I nor ACO (key enzymes of mitochondrial and peroxisomal β-oxidation, respectively) were increased in liver by dietary CLA, and CPT-I expression in liver was also unaffected by either bioactive fatty acid.…”
Section: Discussionmentioning
confidence: 94%
“…Dietary CLA has some beneficial effects on body composition in mammals; decreased body fat and increased lean body mass were observed in mice (Ohnuki et al, 2001;Terpstra et al, 2002), rats (Yamasaki et al, 2003) and pigs (Thiel-Cooper et al, 2001;Tischendorf et al, 2002). CLA also decreased whole body triacylglycerol (TAG) accumulation in hamsters (Bouthegourd et al, 2002) and reduced liver TAG levels in rats (Rahman et al, 2002). However, we did not observe the similar effects in large yellow croaker in the present trail, which agrees with the redults from a few previous studies, such as the findings in salmon fry (Berge et al, 2004), rainbow trout juveniles (Figueiredo-Silva et al, 2005), and smolts (Kennedy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%